Structure and mechanism of arylamine N-acetyltransferases. - Westwood, I; Kawamura, A; Fullam, E; Russell, A; Davies, S; Sim, E (2006)
Arylamine N-acetyltransferases (NATs) are a family of phase II drug-metabolising enzymes which are important in the biotransformation of various aromatic and heterocyclic amines and hydroxylamines, arylhydrazines and arylhydrazides. NATs are present in a wide range of eukaryotes and prokaryotes. Humans have two functional NAT isoforms, both of which are highly polymorphic. The pharmacogenetics of NATs is an area which has been extensively studied. The determination of the X-ray crystal structure of NAT from Salmonella typhimurium led to the identification of the catalytically essential triad of residues: Cys-His-Asp, which is present in all functional NAT enzymes. Recent co-crystallisation data and in silico docking studies of NAT from Mycobacterium smegmatis with substrates and inhibitors have aided the identification of important contact residues within the active site. The X-ray crystal structures of four prokaryotic NAT proteins have now been determined, and these have been used to generate structural models of eukaryotic NATs, providing valuable insight into their active-site architecture. In addition to aiding crystallographic experiments, recent progress in the production of recombinant prokaryotic and eukaryotic NATs has allowed comparative studies of the kinetics and activity profiles of these enzymes. In this review we present an overview of recent structural and activity studies on NAT enzymes, and we outline how in silico methods may be used to predict NAT protein-ligand interactions based on the current knowledge.